Doctors’ Knowledge of Hypertension Guidelines Recommendations Reflected in Their Practice - Nafees Ahmad; Amer Hayat Khan; Irfanullah Khan; Amjad Khan; Muhammad Atif (International Journal of Hypertension)
Aim. To evaluate doctors’ knowledge, attitude, and practices and predictors of adherence to Malaysian hypertension guidelines (CPG 2008). Methods. Twenty-six doctors involved in hypertension management at Penang General Hospital were enrolled in a cross-sectional study. Doctors’ knowledge and attitudes towards guidelines were evaluated through a self-administered questionnaire. Their practices were evaluated by noting their prescriptions written to 520 established hypertensive outpatients (20 prescriptions/doctor). SPSS 17 was used for data analysis. Results. Nineteen doctors (73.07%) had adequate knowledge of guidelines. Specialists and consultants had significantly better knowledge about guidelines’ recommendations. Doctors were positive towards guidelines with mean attitude score of 23.15±1.34 points on a 30-point scale. The median number of guidelines compliant prescriptions was 13 (range 5–20). Statistically significant correlation (rs = 0.635, P<0.001) was observed between doctors’ knowledge and practice scores. A total of 349 (67.1%) prescriptions written were guidelines compliant. In multivariate analysis hypertension clinic (OR = 0.398, P=0.008), left ventricular hypertrophy (OR = 0.091, P=0.001) and heart failure (OR = 1.923, P=0.039) were significantly associated with guidelines adherence. Conclusion. Doctors’ knowledge of guidelines is reflected in their practice. The gap between guidelines recommendations and practice was seen in the pharmacotherapy of uncomplicated hypertension and hypertension with left ventricular hypertrophy, renal disease, and diabetes mellitus.